Pengaruh Kualitas Pelayanan, Harga, Dan Citra Merek Terhadap Kepuasan Pelanggan - Ikraman; Tiawulandari, Anur Rahmah; Syaputra, Harian (YAYASAN HAMJAH DIHA bekerjasama dengan PENA INSTITUTE, 2024)
The purpose of this study was to determine the effect of service quality, price, and brand image on customer satisfaction and to determine which variable is the most dominant on customer satisfaction of online transportation users in Tangerang City. The data used in this study came from filling out a questionnaire instrument, and the valid data collected were 250 respondents. The analysis method in this study uses quantitative primary data. The sampling method in this study is non probability sampling with purposive sampling technique and processed using SPSS application. The results showed that the variables of service quality, price, and brand image partially influenced customer satisfaction. Simultaneously, the variables of service quality, price, and brand image affect customer satisfaction. And the most dominant variable on customer satisfaction is the price variable.